Strategi dan Etika Bisnis Syariah Warung Kopi Tradisional dalam Perspektif Resource-Based View (RBV): Sebuah Tinjauan Sistematis - Putra, Riza Kurnia; Rohmah, Farichatur; Sulatin, Ifa; Wildan, Khayaul; Ningsih, Nur Indah; Perwita, Atika Dyah (BISNIS, 2025)
Traditional coffee shops face double pressure from modern coffee shops and sharia ethical requirements. This study is the first Systematic Literature Review (SLR) to integrate the Resource-Based View (RBV) perspective with sharia ethics to analyze the adaptation strategies of traditional coffee shops. Using the PRISMA protocol, analysis of 10 selected articles revealed fragmentation: strategy studies focused on digital transformation and local identity, while ethics studies emphasized normative compliance. This study bridges this gap by offering a new theoretical contribution: reinterpreting sharia ethics (shiddiq, adl, amanah, halal) as unique and difficult-to-imitate VRIN (Valuable, Rare, Inimitable, Non-substitutable) resources. The integration of Sharia ethics with modern adaptation strategies serves to create sustainable competitive advantage through a digital-ethical hybrid strategy. It is recommended that traditional coffee shops adopt a “hybrid branding” strategy that utilizes digital platforms to promote transparency and halal certification in order to increase customer loyalty.